Race, Colonial History and National Identity: Resident Evil 5 as a Japanese Game - Martin, Paul (Games and Culture, 2018)
Resident Evil 5is a zombie game made by Capcom, featuring a White Americanprotagonist and set in Africa. This article argues that approaching this as a Japanesegame reveals aspects of a Japanese racial and colonial social imaginary that are missedif this context of production is ignored. In terms of race, the game presents hybridracial subjectivities that can be related to Japanese perspectives of Blackness andWhiteness, where these terms are two poles of difference and identity throughwhich an essentialized Japanese identity is constructed in what Iwabuchi calls“strategic hybridism.” In terms of colonialism, the game echoes structures of Japa-nese colonialism through which Japanese colonialism is obliquely memorialized and a“normal” Japanese global subjectivity can be performed.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé